PENGARUH CURRENT RATIO (CR), NET PROFIT MARGIN (NPM) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA PT WILMAR CAHAYA INDONESIA TBK PERIODE 2014-2023 - Ayuni Rosianti Indah Dewi; Rudy Bodewyn Mangsa Tua (LAP4B, 2026)
The research method used is a quantitative approach with an associative method. The type of data used is secondary data obtained from the company’s annual financial reports. The analysis technique applied is multiple linear regression, along with the classical assumption tests consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Hypothesis testing was conducted using the t-test (partial), F-test (simultaneous), and coefficient of determination (R²) with the help of SPSS version 24. The results show that partially Current Ratio no significant effect on Return On Asset with thitung -1.556 < ttabel 2.365 and significance 0.171 > 0.05. Net Profit Margin has a positive and significant effect on Return On Asset with thitung 26.130 > ttable 2.365 and significance 0.000 (<0.05), while TATO also has a positive and signifikan effect on Return On Assets with thitung 8.762 > ttable 2.365 and significance 0.000 < 0.05. Simultaneously, Current Ratio, Net Profit Margin and Total Asset Turnover significantly affect Return On Asset with Fhitung 282.170 > Ftabel 4.76 and significance 0.000 < 0.05. The value of R² 0.993 indicates that 99.3% of Return On Asset, Net Profit Margin and Total Asset Turnover.